Assessing the Mobility of Severe Acute Respiratory Syndrome Coronavirus-2 Spike Protein Glycans by Structural and Computational Methods - Stagnoli, Soledad; Peccati, Francesca; Connell, Sean R.; Martinez-Castillo, Ane; Charro, Diego; Millet, Oscar; Bruzzone, Chiara; Palazon, Asis; Ardá, Ana; Jiménez-Barbero, Jesús; Ereño-Orbea, June; Abrescia, Nicola G. A.; et al. (Frontiers in Microbiology, 2022)
Two years after its emergence, the coronavirus disease-2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) remains difficult to control despite the availability of several vaccines. The extensively glycosylated SARS-CoV-2 spike (S) protein, which mediates host cell entry by binding to the angiotensin converting enzyme 2 (ACE2) through its receptor binding domain (RBD), is the major target of neutralizing antibodies. Like to many other viral fusion proteins, the SARS-CoV-2 spike protein utilizes a glycan shield to thwart the host immune response. To grasp the influence of chemical signatures on carbohydrate mobility and reconcile the cryo-EM density of specific glycans we combined our cryo-EM map of the S ectodomain to 4.1 Å resolution, reconstructed from a limited number of particles, and all-atom molecular dynamics simulations. Chemical modifications modeled on representative glycans (defucosylation, sialylation and addition of terminal LacNAc units) show no significant influence on either protein shielding or glycan flexibility. By estimating at selected sites the local correlation between the full density map and atomic model-based maps derived from molecular dynamics simulations, we provide insight into the geometries of the α-Man-(1→3)-[α-Man-(1→6)-]-β-Man-(1→4)-β-GlcNAc(1→4)-β-GlcNAc core common to all N-glycosylation sites.